Mars' atmospheric calibration of radio tracking data for precise orbit determination. (December 2020) - Cascioli, G.; Petricca, F.; Genova, A.
Abstract: The accurate navigation of Mars' orbiters requires the precise modeling the radio tracking measurements. The Martian atmosphere perturbs the optical path of the radio links leading to significant Doppler shifts ( i.e., up to 5–10 Hz) that affect the spacecraft orbit determination solutions. To process the data occulted by the Martian atmosphere, we present a method that fully calibrates the path delays induced by the neutral atmosphere and ionosphere. Mars' atmospheric models are used to predict the refractive index of these media, and the estimation of scale factors enables a complete compensation of these perturbative effects. This technique allowed us to reanalyze MRO radio tracking data that were previously discarded to avoid aliasing in the results of our gravity investigation. This precise calibration of the Martian atmosphere will also impact the navigation of future missions during aerobraking phases and science operations at low altitudes. Highlights: Mars atmosphere strongly perturbs spacecraft radio tracking data. We propose a method to fully calibrate atmospheric effects on Doppler data. This calibration method is well-suited to recover 10% of the entire MRO dataset. Highly accurate navigation in orbit around Mars will require this data calibration.